Channel models for ultrawideband personal area networks. - Molisch, A.F (IEEE Wireless communications)
This article describes the modeling of ultrawideband wireless propagation channels, especially for the simulation of personal area networks. The IEEE 802.15.3a standards task group has established a standard channel model to be used for the evaluation of PAN physical layer proposals. We discuss the standard model, the measurements that form its basis, and the possibilities for future improvements. This article points out the important differences between UWB channels and narrowband wireless channels, especially with respect to fading statistics and time of arrival of multipath components. The impacts on the different propagation conditions on system design, like RAKE receiver performance, are elaborated.